PEMBUATAN ASAM OKSALAT DARI PELEPAH KELAPA SAWIT (Elaeis guineensis) MELALUI REAKSI OKSIDASI ASAM NITRAT - Yos Pawer Ambarita, Iloan Pandang H M, Seri Maulina (Universitas Sumatera Utara, 2015)
Oxalic acid is a dicarboxylic acid with the molecular formula H2C2O4 which has a wide range of applications in industry. Oxalic acid can be used as fiber bleaching agents, reagents in chemical analysis, and also used in mineral purification of metals. This study aims to determine the effects of temperature and reaction time to quantity and quality of oxalic acid produced by nitric acid oxidation from palm frond powder. The method used for the manufacture of oxalic acid in this study is oxidation method. In this method palm frond powder will be reacted with nitric acid 40 % in the ratio 1: 6 (w/v) at temperature 65, 70, 75, 80, and 85 °C and reaction time 40, 50, 60, 70 and 80 minutes, thus obtained oxalic acid. The research was conducted in several stages: oxidation reaction stage, filtration, precipitation with CaCl2, acidification with H2SO4 and efflorescence. Oxalic acid product quality analyzed using Fourier Transform Infra Red (FTIR) and Plate Melting Point Apparatus. The maksimum yield of oxalic acid was about 23.20 % which obtained at 80 °C and at reaction time 50 minutes.